Effect of Process Parameters and Substrate Material On Opto-Structural Properties of Cuo Thin Film Prepared Following Sol-Gel Spin Coating Technique (Chemical Engineering Research Bulletin, 2023)
Sol-gel spin coating is one of the finest facile techniques for thin films fabrication. Process parameter optimization is essential and incredibly crucial for quality thin films preparation. In this study, single phase monoclinic CuO thin films were prepared following sol-gel spin coating technique, and the process parameters were optimized. Here, the effect of solution spreading mode (static and dynamic) on substrate, rotation speed of spin coater and annealing temperature variation on film quality along with opto-structural properties of the films were investigated thoroughly. A remarkable effect of substrate type (soda-lime-silica, borosilicate, and quartz) on thin films structure has also been reported where soda-lime-silica substrate contaminated thin films and other two seems to be reasonably good. Finally, uniform CuO thin films were prepared on quartz substrate in static spin coating mode following two-step spin coating technique and by annealing at the optimized temperature of 500oC for one hour in a tube furnace. Opto-structural properties i.e., phase purity, crystallinity, crystallite size, transmittance and optical band gap of the films were characterized using X-ray diffraction (XRD) and ultraviolet visible spectroscopy (UVVis). For annealing temperature of 500°C at 1h on quartz substrate for static mode, single phase CuO films were prepared successfully having maximum crystallinity of 88.23% and minimum band gap of 1.98 eV.Chemical Engineering Research Bulletin 23 (2023): 69-72